GENERATION OF PSEUDORANDOM NUMBERS - Gladskih Yur’evich Gladkih (Современная наука и инновации, 2022)
The article is devoted to algorithms for generating pseudorandom numbers according to certain laws of distribution of random numbers. The problems of generation of pseudorandom uniformly distributed integers of large size and real numbers, real numbers in accordance with the laws of exponential and uniform distribution.